SYNTHESIS, CHARACTERIZATION, AND ANTICANCER ACTIVITY OF SOME NOVEL ACRIDINE DERIVATIVES - PADIGELA, SWETHA; RM, BHAGAVAN RAJU; VVS, RAJENDRA PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to synthesize and evaluate the anticancer activity of some novel acridine derivatives. Methods: The present works involve condensation of acridine and various 2, 4-Thiazolidine-2,4-dione derivatives (2a–2h) with chloroacetyl chloride to give a novel acridine derivatives (5a–5l), respectively. Results: All the newly synthesized molecules (5a–5l) were characterized by FTIR, H1-NMR, and mass spectral analysis along with physical data. The biological potentials of the new synthesized compounds are evaluated for their in vitro anticancer activity by MTT assay. Conclusion: The synthesized compounds 5a, 5f, and 5h exhibited good anticancer activity against MCF-7 and SKVO3 cancer cell lines at a concentration of 0.5 mg/mL-1.